Evaluation of role of peri portal infiltration of ropivacaine in post laparoscopic cholecystectomy pain management: a randomized controlled double-blind study - Nayal, Deepankar; Bijalwan, Anurag; Singhal, Pradeep; Kumar , Ajay (International Surgery Journal, 2023)
Background: Laparoscopic cholecystectomy is considered as the treatment of choice for symptomatic cholelithiasis. The present study was conducted to assess the role of peri-portal infiltration of ropivacaine in post laparoscopic cholecystectomy pain management. Methods: A total of 100 eligible cases undergoing laparoscopic cholecystectomy were randomly allocated in two groups: group A (received infiltration of total 20 ml of 0.5% ropivacaine, 5 ml in each port site after removal of trocar, and group B (received placebo i.e., 20 ml normal saline). Postoperative pain was assessed using Wong Baker facial pain scale at 6, 12 and 18 hours and use of rescue analgesics were noted. Results: Group I comprised of 27 males and 23 females and group II had 25 males and 25 females. The mean heart rate in group I was 85.4 and in group II was 86.2. Respiratory rate was 14.2 cycles/minute in group I and 15.2 cycles/minute in group II. The mean blood pressure was 134.2/74.6 mmHg in group I and 136.4/75.2 mmHg in group II and oxygen saturation was 99.2% in group I and in group II was 99.5%. The mean VAS scores were significantly lower in group A cases as compared to group B, throughout the study follow up (p<0.01). 70% in group A and 90% in group B required 1 dose and 10% in group II required 2 doses. Duration of rescue analgesia was 21.49 minutes in group A and 17.3 minutes in group B. Conclusions: Peri-portal infiltration of ropivacaine is effective in reducing post laparoscopic cholecystectomy pain. Mean duration of analgesia was significantly more and requirement of rescue analgesics were significantly less in cases managed by peri-portal infiltration of ropivacaine as compared to control group (using NSAIDs).